2020
DOI: 10.1371/journal.pone.0242845
|View full text |Cite
|
Sign up to set email alerts
|

Short- versus long-term dual antiplatelet therapy after second-generation drug-eluting stent implantation in patients with diabetes mellitus: A meta-analysis of randomized controlled trials

Abstract: Background Diabetes is considered to be a high-risk factor for thromboembolic events. However, available data about the optimal dual antiplatelet therapy (DAPT) in patients with diabetes mellitus (DM) after second-generation drug-eluting stent (DES) implantation are scant. Objective The purpose of this study was to compare the impact of various DAPT durations on clinical outcomes in patients with DM after second-generation DES implantation. Methods We searched PubMed, Embase, and the Cochrane Library for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…No significant difference was found in the primary end point and secondary end point points, including ST, TVR, MI, stroke, and overall mortality. This is found to be consistent with the previously conducted trials, such as those of by Sharma et al 1 and Zhang et al, 18 which primarily focused on the diabetic patients and established that there was no significant difference in clinical outcomes like MI, ST, TVR, and mortality between 2 treatment groups. The ITALIC trial, 11 in which one-third of the population had diabetes, reported the percentage of the primary end point at 1.5% and 1.6% comparing 6 and 12 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No significant difference was found in the primary end point and secondary end point points, including ST, TVR, MI, stroke, and overall mortality. This is found to be consistent with the previously conducted trials, such as those of by Sharma et al 1 and Zhang et al, 18 which primarily focused on the diabetic patients and established that there was no significant difference in clinical outcomes like MI, ST, TVR, and mortality between 2 treatment groups. The ITALIC trial, 11 in which one-third of the population had diabetes, reported the percentage of the primary end point at 1.5% and 1.6% comparing 6 and 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is imperative to establish an appropriate duration of DAPT in the diabetic population to optimize the safety profile and decrease the risk of bleeding associated with DAPT without compromising the efficacy of second-generation DES for coronary artery disease (CAD). 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox regression analysis revealed that age, previous myocardial infarction, previous revascularization, and a history of cerebrovascular disease were independent predictors of MACCEs. Patients with previous myocardial infarction were included in the PRODIGY [27] and the PEGASUS-TIMI 54 [28] studies to explore the application duration and DAPT regimen, and they showed that prolonged DAPT was associated with a reduction in major adverse cardiovascular events. Additionally, the DAPT study [29] established the PARIS-CTE [30] and the OPT-CAD [31] DAPT scores.…”
Section: Characteristicmentioning
confidence: 99%